2012
DOI: 10.1093/nar/gks888
|View full text |Cite
|
Sign up to set email alerts
|

Persistent androgen receptor-mediated transcription in castration-resistant prostate cancer under androgen-deprived conditions

Abstract: The androgen receptor (AR) is a ligand-inducible transcription factor that mediates androgen action in target tissues. Upon ligand binding, the AR binds to thousands of genomic loci and activates a cell-type specific gene program. Prostate cancer growth and progression depend on androgen-induced AR signaling. Treatment of advanced prostate cancer through medical or surgical castration leads to initial response and durable remission, but resistance inevitably develops. In castration-resistant prostate cancer (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
125
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 97 publications
(131 citation statements)
references
References 81 publications
2
125
0
1
Order By: Relevance
“…The differential activation of biological pathways further supports a divergent transcriptional program regulated by AR in CRPC, which likely serves to meet the changing needs of cancer cells as the disease progresses. Consistent with the patient tumor findings, others have also reported distinct AR binding events in CRPC cell line models, C4-2B and LNCaP-abl (Decker et al 2012). Specifically, AR binding events in CRPC activated mitotic cell cycle genes that help to drive cell proliferation (Decker et al 2012).…”
Section: Distinct Genomic and Transcriptional Programs In Crpcsupporting
confidence: 70%
See 1 more Smart Citation
“…The differential activation of biological pathways further supports a divergent transcriptional program regulated by AR in CRPC, which likely serves to meet the changing needs of cancer cells as the disease progresses. Consistent with the patient tumor findings, others have also reported distinct AR binding events in CRPC cell line models, C4-2B and LNCaP-abl (Decker et al 2012). Specifically, AR binding events in CRPC activated mitotic cell cycle genes that help to drive cell proliferation (Decker et al 2012).…”
Section: Distinct Genomic and Transcriptional Programs In Crpcsupporting
confidence: 70%
“…While it is accepted that continued activation of AR signaling axis facilitates the development of CRPC, a critical question that remains is whether diverse AR-mediated transcriptional program and gene networks are in play in androgen-dependent and CRPC. While the early study by Holzbeierlein et al (2004) reported similarities in overall gene profiles of androgendependent and CRPC, recent studies are beginning to identify important differences in the expression of specific genes following transition of prostate cancer from an androgen-dependent state to one that is androgenindependent, reflecting distinct AR transcriptional regulatory programs in the two stages of prostate cancer , Decker et al 2012, Sharma et al 2012.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of these studies have been conducted on prostate cancer cell lines and considerable effort has been made in defining AR targets in tumour epithelium [12][13][14][15][16][17]. This has revealed a transcriptional role for AR in tumour cells regulating cell proliferation, metabolism, survival and DNA repair [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…This has revealed a transcriptional role for AR in tumour cells regulating cell proliferation, metabolism, survival and DNA repair [18,19]. Prostate cancer cell lines have also been used to determine the changes in AR transcriptional networks in both a hormonenaïve-and castrate-resistant setting and numerous studies have revealed distinct binding profiles in the androgen-independent setting [13,17,18,20,21]. More recently, the genomic binding profile of AR variants have also been explored and have been shown to compensate for full length AR in an endocrine therapy-like setting [22].…”
Section: Introductionmentioning
confidence: 99%
“…ChIP analyses were conducted as described previously (42). In brief, HEK293T cells were transfected with human GR cDNA in charcoal-stripped medium for 40 h and treated with vehicle or 10 nM dexamethasone for 4 h. The cells …”
Section: Prediction Of Mirnas Target Genes and Functionalmentioning
confidence: 99%